Value-Oriented Model of Tuition in the Context of University 3.0 Paradigm - Aleksey I. Balashov (National Research Mordova State University, 2019)
Introduction. This article presents the analysis of transformational changes in the Russian system of higher education. The authors aimed to develop a value-oriented model for the organization of educational activities. The concept of University 3.0 serves as a modern basis for ensuring the global competitiveness of national economies in the digital world. Materials and Methods. The methodological approaches of the study were systematic, comparative and problem-chronological methods. Results. The study expanded the understanding of the main stages of transformation in the higher education system in the Russian Federation. The results show that the destruction of the Soviet academic culture was accompanied by the destruction of the historical institutional balance. As a result, it became necessary to form new norms that define both the rules of interaction within the educational community and the place of this community in the overall social structure. The concept of Education 3.0 is designed to form these normative frameworks and ensure their interiorisation both in the pedagogical community and among students. It is revealed that in the modern Russian educational environment they are formed spontaneously, mainly due to the independent development of new technologies by students, while teachers continue to adhere to the previous educational concepts. Discussion and Conclusion. The practical significance of the study lies in the proposal of specific measures, the implementation of which will form the reputation of the University, attract additional investment, enhance its competitiveness both at the domestic and international level. The timeliness of the study lies in the fact that the analysis of the educational reform was carried out taking into account the needs of value-based management. The results of the study will be useful for the management of higher education institutions to reformulate development concepts, as well as for the executive authorities to further reform the educational system.